PENGARUH BEBAN KERJA TERHADAP RI PENGARUH BEBAN KERJA TERHADAP RISIKO PSIKOSOSIAL PADA KARYAWAN: PENGARUH BEBAN KERJA TERHADAP RISIKO PSIKOSOSIAL PADA KARYAWAN - Ira Risnawati (Jurnal Penelitian Kesmasy, 2025)
Psychosocial hazards in the workplace arise from the interaction between the work environment, job content, and organizational conditions with the capacity, needs, culture, and personal factors of workers, and can affect health, performance, and job satisfaction. This study aims to analyze psychosocial factors related to the level of psychosocial risk in employees of University X. This quantitative cross-sectional study was conducted in the period January–May with a sample of 188 respondents. Psychosocial risk was measured using the Pandemic-Related Perceived Stress Scale, while psychosocial factors were collected through the COPSOQ III questionnaire that has undergone validity and reliability tests. The results show that variables in the home and social arenas are not significant to the level of psychosocial risk. In the individual arena, age is significantly related to the level of risk. In the work arena, workload is a variable that shows a significant relationship with the level of psychosocial risk.